Genome-Wide Insights Into the Organelle Translocation of Photosynthetic NDH-1 Genes During Evolution - Yu, Jie; Ran, Zhaoxing; Zhang, Jingsong; Wei, Lanzhen; Ma, Weimin (Frontiers in Microbiology, 2022)
Translocation of chloroplast-located genes to mitochondria or nucleus is considered to be a safety strategy that impedes mutation of photosynthetic genes and maintains their household function during evolution. The organelle translocation strategy is also developed in photosynthetic NDH-1 (pNDH-1) genes but its understanding is still far from complete. Here, we found that the mutation rate of conserved pNDH-1 genes was gradually reduced but their selection pressure was maintained at a high level during evolution from cyanobacteria to angiosperm. By contrast, oxygenic photosynthesis-specific pNDH-1 genes had an opposite trend, explaining the reason why they were transferred from the reactive oxygen species (ROS)-enriched chloroplast to the ROS-barren nucleus. Further, genome-wide sequence analysis supported the possibility that all conserved pNDH-1 genes lost in chloroplast genomes of Chlorophyceae and Pinaceae were transferred to the ROS-less mitochondrial genome as deduced from their truncated pNDH-1 gene fragments. Collectively, we propose that the organelle translocation strategy of pNDH-1 genes during evolution is necessary to maintain the function of pNDH-1 complex as an important antioxidant mechanism for efficient photosynthesis.